Unified Power Modeling Design for Various Raspberry Pi Generations Analyzing Different Statistical Methods - Paniego, Juan Manuel (2019)
Monitoring processor power is important to define strategies that allow reducing energy costs in computer systems. Today, processors have a large number of counters that allow monitoring system events such as CPU usage, memory, cache, and so forth. In previous works, it has been shown that parallel application consumption can be predicted through these events, but only for a given SBC board architecture. In this article, we analyze the portability of a power prediction statistical model on a new generation of Raspberry boards. Our experiments focus on the optimizations using different statistical methods so as to systematically reduce the final estimation error in the architectures analyzed. The final models yield an average error between 2.24% and 4.45%, increasing computational cost as the prediction error decreases.